Treatment of a Patient with Acute Promyelocytic Leukemia with Multiple Isolated Relapses in the Central Nervous System: A Case Report and Mini-Review of the Literature - Qixin Sun; Wenyi Chen; Ahui Wang; Zili Yang; Guiping Chen; Zhigang Zhu (Case Reports in Hematology)
The efficacy of therapeutics for acute promyelocytic leukemia (APL) has exhibited an increase in recent years. Only a few patients experience relapse, including extramedullary relapse, and in patients with extramedullary relapse, the central nervous system (CNS) is the most common site. To date, there is no expert consensus or clinical guidelines available for CNS relapse, at least to the best of our knowledge. The optimal therapeutic strategy and management options for these patients remain unclear. The present study reports the treatment of a patient with APL with multiple isolated relapses in the CNS. In addition, through a mini-review of the literature, the present study provides a summary of various reports of this disease and discusses possible treatment options for these patients.